Alih Teknologi Wadah Budidaya Ikan Gurami di POKDAKAN Mina Perkasa Purbalingga - Pratama, Ikhsan; Biky, Muhammad Amir (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to improve the knowledge and skills of POKDAKAN Mina Perkasa members in applying CBIB to gourami cultivation, as well as to increase production through a revitalization program for fish farmers. The method used in this activity was the Participatory Learning and Action method which was attended by all 20 members of POKDAKAN Mina Perkasa. Evaluation was carried out by distributing questions through a questionnaire to each participant after the training activity to measure the understanding of the training material. The results of the questionnaire were then analyzed descriptively to see how many participants understood the training material. The results of this community service activity showed that the level of understanding of POKDAKAN members after the activity was above 80%. In addition, POKDAKAN members were also committed to implementing the CBIB concept in gourami cultivation. This activity had an impact on POKDAKAN Mina Perkasa which could be felt directly in the form of innovation in cultivation technology, increased knowledge and skills in cultivation and increasing independence and sustainability of cultivation businesses.